GASTO PÚBLICO Y CRECIMIENTO EN AMÉRICA LATINA: LA LEY DE WAGNER Y LA HIPÓTESIS DE KEYNES - Ramírez Cedillo, Eduardo; López Herrera, Francisco (Investigación Económica, 2021)
Se analiza la relación del crecimiento económico con el gasto público de 16 países latinoamericanos de 1990 a 2017. Este trabajo contribuye a la literatura sobre el tema enfocándose en la región. Los resultados de un modelo para paneles cointegrados respaldan la ley de Wagner en el largo plazo y brindan evidencia parcial a favor de las hipótesis de Keynes en el corto plazo. PUBLIC SPENDING AND GROWTH IN LATIN AMERICA: WAGNER´S LAW AND KEYNES’S HYPOTHESIS ABSTRACT The relationship between economic growth and public spending in 16 Latin American countries from 1990 to 2017 is analyzed. This paper contributes to the literature on the subject focusing on the region. The results from a model of cointegrated panels support Wagner’s Law in the long term and provides partial evidence in favor of the Keynesian hypotheses in the short term.